2008
DOI: 10.7151/dmgt.1405
|View full text |Cite
|
Sign up to set email alerts
|

Secure domination and secure total domination in graphs

Abstract: A secure (total ) dominating set of a graph G = (V, E) is a (total) dominating set X ⊆ V with the property that for each u ∈ V − X, there exists x ∈ X adjacent to u such that (X − {x}) ∪ {u} is (total) dominating. The smallest cardinality of a secure (total) dominating set is the secure (total ) domination number γ s (G) (γ st (G)). We characterize graphs with equal total and secure total domination numbers. We show that if G has minimum degree at least two, then γ st (G) ≤ γ s (G). We also show that γ st (G) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…Then we prove that for every graph G, γ s (G) ≤ γ (G) + β 0 (G) − 1, which improves a previous bound of Klostermeyer and Mynhardt [7]. Bounds relating the secure domination to the independence number are also presented for triangle-free graphs.…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…Then we prove that for every graph G, γ s (G) ≤ γ (G) + β 0 (G) − 1, which improves a previous bound of Klostermeyer and Mynhardt [7]. Bounds relating the secure domination to the independence number are also presented for triangle-free graphs.…”
Section: Introductionsupporting
confidence: 61%
“…As we shall show, we extend these two bounds to triangle-free graphs and graphs with girth at least six, respectively. Moreover, Klostermeyer and Mynhardt [7] observed that for every graph G, γ s (G) ≤ 2β 0 (G), and posed the problem of finding graphs for which the bound is sharp. In the next, we show that it is possible to improve Klostermeyer and Mynhardt's bound which will explain in some sense why there has been a difficulty finding a graph reaching their bound.…”
Section: Secure Domination and Independencementioning
confidence: 99%
See 1 more Smart Citation
“…secure total domination number ) of G. A secure dominating set of cardinality γ s (G) is called a γ s -set. Secure domination and secure total domination in graphs have been studied in [4,5,10,12,19].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, for the graph shown in Figure 1, on the right, a γ s (G)-function (set) can place one guard at each white-coloured vertex. This concept of protection was introduced by Cockayne et al in [9], and studied further in [3,4,6,8,19,26]. The problem of computing γ r (G) is NP-hard, even when restricted to bipartite or chordal graphs [16], and the problem of computing γ s (G) is also NP-Hard, even when restricted to split graphs [3].…”
mentioning
confidence: 99%